2016
DOI: 10.1007/s10068-016-0099-2
|View full text |Cite
|
Sign up to set email alerts
|

UVC dosage effects on the physico-chemical properties of lime (Citrus aurantifolia) juice

Abstract: Lime juice is in high demand due to a sour taste. Commercial thermal pasteurization extends juice shelf-life; however, fruit juice subjected to thermal pasteurization tends to change color and lose vitamin content. Lime juice was irradiated with ultraviolet-C (UVC) at dosages of 22.76, 30.19, and 44.24 mJ/cm to investigate effects on the physicochemical properties of lime juice. pH values of lime juice did not change while total soluble solids, turbidity, titratable acidity, sweetness, and color values of lime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Feng et al () obtained 0.90 total color change in the melon juice treated with 37.5 J/mL UV‐C dose in a coiled‐type reactor and Caminiti et al () reported total color change of 0.68 in the apple juice after the UV‐C treatment with 5.31 J/cm 2 supplying 5log inactivation in E. coli by a rising‐film reactor. In addition, Mohd‐Hanif, Shamsudin, and Adzahan () observed a total color change of 1.78 as a result of 22.76 mL/cm 2 UV dose treatment to lime juice in a Dean vortex reactor. The total color change obtained in this study (1.15 ± 0.27) after the UV‐C treatment of onion juice with 38.095 kJ/L dose in the coiled‐type reactor is in line with the similar studies.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al () obtained 0.90 total color change in the melon juice treated with 37.5 J/mL UV‐C dose in a coiled‐type reactor and Caminiti et al () reported total color change of 0.68 in the apple juice after the UV‐C treatment with 5.31 J/cm 2 supplying 5log inactivation in E. coli by a rising‐film reactor. In addition, Mohd‐Hanif, Shamsudin, and Adzahan () observed a total color change of 1.78 as a result of 22.76 mL/cm 2 UV dose treatment to lime juice in a Dean vortex reactor. The total color change obtained in this study (1.15 ± 0.27) after the UV‐C treatment of onion juice with 38.095 kJ/L dose in the coiled‐type reactor is in line with the similar studies.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, it has also been used as a postharvest measure to maintain fruit quality. There have been a number of reports about the treatments of UVB and UVC exposure [20,21,22,23], but a global evaluation of fruit quality when exposed to other polychromatic light sources was previously lacking. In the present study, the effects of LED and UV light treatments on the soluble sugar, organic acid, and carotenoid content was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The changes of color in UVC-LEDs-treated juices may be due to the isomerization of carotenoid and its interactions with free radicals caused by UVC-LED treatments (Bhat, 2016). In contrast, the value of ÁE Ã in lime juices reached 5.02 after exposing to UVC treatment (254 nm) in the continuous flow condition at 30.19 mJ/cm 2 (Mohd-Hanif et al, 2016).…”
Section: Effects Of Uvc-led Treatment On Color Parameters Of Orange Juicementioning
confidence: 95%